2020
DOI: 10.1016/j.ecolecon.2019.106566
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and agriculture in the Sudan: Impact pathways beyond changes in mean rainfall and temperature

Abstract: Several environmental changes have occurred in the Sudan in the past; several are ongoing; and others are projected to happen in the future. The Sudan has witnessed increases in temperature, floods, rainfall variability, and concurrent droughts. In a country where agriculture, which is mainly rainfed, is a major contributor to gross domestic product, foreign exchange earnings, and livelihoods, these changes are especially important, requiring measurement and analysis of their impact. This study not only analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 32 publications
1
38
0
4
Order By: Relevance
“…Changes in money supply and international agricultural prices caused by macroeconomic monetary policy can also impact domestic agricultural prices ( Durevall et al, 2013 ); for example, Liu et al (2020) found that exchange rate changes triggered agricultural price fluctuations. External uncertainty factors have also been found to be associated with the direct impact of natural disasters and climate change on agricultural product production and prices ( Chatzopoulos et al, 2020 ; Klomp and Hoogezand, 2018 ; Siddig et al, 2020 ). In recent years, the external information impact on agricultural prices from public health emergencies has attracted research attention; for example, Seok et al concluded that retailers and wholesalers in the Korean egg industry had used their market power to raise egg prices during a food safety crisis ( Seok et al, 2018 ), and Yi et al (2019) found that public opinion on the avian influenza led directly to a price risk for broilers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Changes in money supply and international agricultural prices caused by macroeconomic monetary policy can also impact domestic agricultural prices ( Durevall et al, 2013 ); for example, Liu et al (2020) found that exchange rate changes triggered agricultural price fluctuations. External uncertainty factors have also been found to be associated with the direct impact of natural disasters and climate change on agricultural product production and prices ( Chatzopoulos et al, 2020 ; Klomp and Hoogezand, 2018 ; Siddig et al, 2020 ). In recent years, the external information impact on agricultural prices from public health emergencies has attracted research attention; for example, Seok et al concluded that retailers and wholesalers in the Korean egg industry had used their market power to raise egg prices during a food safety crisis ( Seok et al, 2018 ), and Yi et al (2019) found that public opinion on the avian influenza led directly to a price risk for broilers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Millions of people in Sudan mainly depend on the agricultural sector for their livelihood, including cultivation, transportation, and marketing. It is expected that the population of Sudan, approximately 43 million people, will double by the year 2050 [16]. This increment will put pressure on available natural resources to produce sufficient amounts of agricultural outputs to meet the rising demand for food.…”
Section: Introductionmentioning
confidence: 99%
“…This increment will put pressure on available natural resources to produce sufficient amounts of agricultural outputs to meet the rising demand for food. Indeed, reports show that the county has witnessed rainfall fluctuations, rising in temperature, increasing frequency of floods, and recurrent droughts which have significantly affected agricultural production [16], especially in the rainfed sector. For instance, crop farming supports livelihood sources for about 80% of its population and households, directly through agricultural production and indirectly through labour workforce in the agricultural sector.…”
Section: Introductionmentioning
confidence: 99%
“…Since independence in 1956 Sudan has depended entirely on agriculture, with cotton-mainly serving British textile mills-as the money crop, which Sudan's largest economic undertaking, the Gezira Scheme was established to support (Siddig et al 2020). Instead of rebuilding a diversified economy after independence, Sudan's national government persisted with an agricentric economic model.…”
Section: History Of Sudan's Economy Labor Market and Educationmentioning
confidence: 99%